Generation of high quality random numbers via an all‐silicon‐based approach. Issue 12 (1st August 2016) - Bisadi, Zahra; Meneghetti, Alessio; Tomasi, Alessandro; Tengattini, Andrea; Fontana, Giorgio; Pucker, Georg; Bettotti, Paolo; Sala, Massimiliano; Pavesi, Lorenzo
Abstract: A quantum random number generator (QRNG) based on a silicon nanocrystals (Si‐NCs) light emitting device (LED) coupled with a silicon single photon avalanche photodiode (Si‐SPAD) is presented. A simple setup is used for the generation of random bits. The modeled approach assures a negligible bias on datasets of ∼ 100 Mbits length. The raw data pass all the statistical tests in the National Institute of Standards and Technology (NIST) suite without any post‐processing operations. The bit‐rate of 0.6 Mbps is achieved. The information‐theoretically provable randomness extractor of Toeplitz‐hashing function is applied to longer datasets ( ∼ 1 Gbits) to extract the randomness, to minimize the bias, and consequently pass all the NIST tests. Stabilizing the temperature, resetting the applied current to the LED, or a feedback system can also be used as parameter control solutions to generate good quality, long datasets of random numbers suitable for cryptographic applications.